2007
DOI: 10.1021/jp0668192
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic versus Nonelectrostatic Effects in DNA Sequence Discrimination by Divalent Ions Mg2+ and Mn2+

Abstract: Mg 2+ and Mn 2+ ions are critical to the functioning of phosphoryl transfer enzymes, such as restriction endonucleases. Although these ions play similar roles in the chemical steps, they govern substrate specificity via modulating sequence discrimination by up to a factor of 10 5 with Mg 2+ and only up to a factor of 10 with Mn 2+ . To explain whether such diversity originates in fundamental differences in the electronic structures of the nucleobase-hydrated-metal ion complexes, structures and interaction ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 72 publications
6
18
0
Order By: Relevance
“…These results coincide with findings from bulk measurements that show that adenine is a weaker binder than guanine. 48,53,71,72 The lack of length dependency corroborates our earlier published findings that suggest the difference in free energies are due to variations in electron density of these surface-bound nucleobases. 42 Figure 2b shows that the number of Mg(II) ions bound depends linearly on guanine strand length.…”
Section: Resultssupporting
confidence: 88%
“…These results coincide with findings from bulk measurements that show that adenine is a weaker binder than guanine. 48,53,71,72 The lack of length dependency corroborates our earlier published findings that suggest the difference in free energies are due to variations in electron density of these surface-bound nucleobases. 42 Figure 2b shows that the number of Mg(II) ions bound depends linearly on guanine strand length.…”
Section: Resultssupporting
confidence: 88%
“…Previous quantum chemical calculations of Mg 2+ and Mn 2+ in complex with water molecules revealed that the hydration geometry of the Mn 2+ ion deviates from the ideal octahedral arrangement, due to the excessive polarization and charge-transfer effects of Mn 2+ with open d orbitals3031. This difference between Mg 2+ and Mn 2+ was suggested to affect the substrate specificity of restriction enzymes32. We expect that this difference in the electronic states and polarization would also contribute to the difference in the affinities of the M1 site for Mg 2+ and Mn 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Although the Mg 2 + cation predominantly exists in its hexahydrated form [Mg(H 2 O) 6 ] 2 + in bulk water, it loses one water molecule when bonded to N7(G) of the nucleotide, and therefore five explicit water molecules are included to saturate the first hydration shell of the cation. [35] As recently advocated by Oliva and Cavallo for a similar model, [29] solvent effects beyond the first hydration shell should also be included to study ion-nucleic acid interactions. Consequently, the well-known polarizable continuum model (PCM) [36] was also included in our model following two strategies.…”
Section: Methodsmentioning
confidence: 99%